Corporate governance: a farce at Volkswagen?. Issue 6 (13th November 2017) - Arora, Jaskiran
Abstract : Synopsis: This case on "Corporate governance: a farce at Volkswagen (VW)" is set in September of 2015. The precipitating events, which started with the Emissions scandal and tampering of the technology, unfold a history of threatening organizational culture, deliberate cheating, and failure of good governance. The case presents that though the outgoing CEO took the responsibility for the event but said that he was shocked by the event and stunned that the misconduct of such a scale could occur in the VW Group. Given the roles and responsibilities of board of management and the supervisory board, how could the scandal of such magnitude go unnoticed? Were robust corporate governance practices being not followed at VW? Research methodology: The case is based on the material available in the public domain, records, press reports, published books, interviews published by key board members of Volkswagen and the company website. Relevant courses and levels: This case can be used for undergraduate senior classes or graduate and executive education level courses in corporate governance and ethical practices. This case will sync best with the topics around Board Composition and size, Board Independence, fiduciary duties of supervisory board, board duality and leadership and its impact on organizational culture.